Postoperative Complications of Flap Procedures in Chest Wall Defect Reconstruction: A Two-Center Experience - Breidung, David; Delavari, Sarina; Grimme, Sebastian; Habild, Götz; Billner, Moritz; Kraus, Dietmar; Reichert, Bert; Megas, Ioannis Fivos (Medicina, 2024)
Background and Objectives: Chest wall defect reconstruction is a complex procedure aimed at restoring thoracic structural integrity after trauma, tumor removal, or congenital issues. In this study, postoperative complications were investigated to improve the care of patients with these critical conditions. Materials and Methods: A retrospective study of chest wall reconstructions from 2004 to 2023 was conducted at Klinikum Nürnberg and Evangelisches Waldkrankenhaus Spandau—Berlin. Data included patient demographics, comorbidities, defect etiology, surgery details, and complications using the Clavien–Dindo classification. Results: Among the 30 patients included in the study, a total of 35 complications occurred in 35 thoracic wall defect reconstructions. These complications were classified into 22 major and 13 minor cases. Major complications were more common in patients with cancer-related defects, and considerable variations were observed between free flap and pedicled flap surgeries. Notably, the use of the anterolateral thigh (ALT) flap with vastus lateralis muscle demonstrated promise, exhibiting fewer complications in select cases. The reconstruction of chest wall defects is associated with substantial complications regardless of the etiology of the defect and the particular surgical procedure used. Interestingly, there was a lower complication rate with free flap surgery than with pedicled flaps. Conclusions: The ALT flap with vastus lateralis muscle deserves further research in this field of reconstruction. Multidisciplinary approaches and informed patient discussions are crucial in this complex surgical field, emphasizing the need for ongoing research and technique refinement.
CRIS-Team Scopus Importer:2024-12-13
Keywords: chest wall; free flap; pedicled flap; reconstruction; soft tissue reconstruction